The Influence of Operating Cycle, Cash Flow Volatility, and Audit Fee on Earnings Persistence (The Indonesian Cases) - I Gusti Ketut Agung Ulupui; Douglas Douglas; Hafifah Nasution (Faculty of Economics, Universitas Sriwijaya, 2020)
Research is aiming at analyzing the influence of operating cycle, cash flow volatility, and audit fee on earnings persistence by studying manufacturing companies listed on Indonesia Stock Exchange (IDX). This research studied secondary data from documents in the forms of annual reports and financial reports of the companies taken from IDX website. After conducting a purposive sampling method, 12 companies were chosen to be the samples with 60 total observations. The data were analyzed by using descriptive statistics and panel data regression using Common Effect Model (CEM) processed by Eviews 10. Earnings persistence as the dependent variable was proxied by the regression coefficient from the regression model of previous year earnings towards the current earnings. The independent variable operating cycle was proxied by the means of accounts receivable turnovers and the means of the inventory turnovers. The cash flow volatility was proxied by the standard deviation of the cash flow operation divided by the total assets. The audit fee was proxied by the natural logarithm of the amount of audit fee. The panel data regression analysis showed that operating cycle has significant influence on earnings persistence. The results explain that companies with shorter operating cycle have high earnings persistence. The results also showed that cash flow volatility and audit fee have no influence on earnings persistence. A short operating cycle can make a company’s earnings persistence higher. The implication of this research is a shorter operating cycle can increase the earnings persistence of a company and can increase the interests of investors towards the company.